(untitled) (Global Journal of Human-Social Science, 2019)
Education especially technical and vocational education is central to national development of fast developing countries such as the Asian Tigers In Africa and Nigeria in particular the adoption of technical and vocational education has not been given environmental recognition This paper argues that the acquisition of technical and vocational skills education system propelling self reliant development This paper seeks to understand the role of technical and vocational educations have in national development The paper examines the problems of technical and vocational education in Nigeria